Meningkatkan Akhlak Peserta Didik Melalui Kegiatan Ekstrakurikuler Mengaji - Mhd Ihsanul Fikri; Ella Rinanda; Sutan M Fakhrurrozy (Philosophiamundi, 2023)
Changes that occur in the morals of students today are something that cannot be avoided but the negative impact can be minimized through various efforts and approaches. This study aims to describe how the morals and morals of students can be formed and improved through extracurricular activities, the object chosen is junior high school students, this is because when entering that age is very vulnerable to changes that occur in their environment. This research uses a method with a qualitative approach, namely with a type of phenomenology, which reveals the meaning that occurs in the research location based on existing phenomena. Data were collected through observation, and interviews. The result of the study is that the moral development of students through extracurricular activities can be carried out smoothly, Starting from the required learning materials with moral majesty and through extracurricular activities, the morals of students experience good changes